The role of surface forces in mineral flotation. (December 2019) - Xing, Yaowen; Xu, Mengdi; Gui, Xiahui; Cao, Yijun; Rudolph, Martin; Butt, Hans-Jürgen; Kappl, Michael
Abstract: Flotation is an interfacial separation technique, which plays a major role in mineral processing industry. It separates particles according to their wetting properties. In flotation pulp, particles and bubbles are highly dispersed in aqueous medium and in the presence of various flotation reagents. Almost all interfacial interactions including inter-particle, inter-bubble, and bubble-particle interactions in the complex pulp medium are driven by surface forces. Therefore, a fundamental understanding of the role of surface forces in flotation is a prerequisite to enhance practical flotation performance and adapt it for treatment of complex and refractory ores. In this paper, recent advances in the field of surface forces encountered in mineral flotation are reviewed. In particular, we highlight the latest progress in the attachment mechanism between bubble and particle with the aid of atomic force microscope and interference microscope. The current knowledge gap and future directions are also discussed.